ANALISIS KEPADATAN DAN KERAGAMAN FUNGI MIKORIZA ARBUSKULA (FMA) PADA BEBERAPA TANAMAN PERKEBUNAN DI DESA BAKUBAKULU KECAMATAN PALOLO KABUPATEN SIGI - Masrikail, Muhammad Zul; Patadungan, Yosep Soge; Isrun, Isrun (AGROTEKBIS, 2019)
This study aims to determine the density and diversity of spores of Arbuscular Mycorrhizal Fungi (AMF) at rhizosphere of several plantation crops, such as ; cocoa (Theobroma cacao L.), coconut (Cocos nucifera L.), aren (Arenga pinnata Merr), candlenut (Aleurites moluccana L.), and bush. Soil sampling was taken by descriptive exsplorative method. Soil samples of rhizospheres of several industrial plants, had been taken from January to March, 2018. Enumerations of spores conducted in Laboratory of Soil Science Department, Faculty of Agriculture, University of Tadulako. Horizontally, the most spores numbers of AMF were found on the rhizosphere coconut in a distance of two meters from stand of plant, that weres 119 spores in 10 g of soil, the lowest spores number were found on the rhizosphere of cocoa in a distance of one meters from stand of plant, that were 15 spores in 10 g of soil. Vertically, the most spores numbers were found on the rhizosphere of aren plant in a depth of 40 cm, that were 98 spores in 10 g of soil. The lowest spore number were found on the rhizosphere of cocoa in a depth of 40 cm, that were 14 spores in 10 g of soil. The analysis of the diversity of colors found there are nine kinds of different colors, includes the yellow clear color, yellow, yellow green, reddish yellow, red, red brown, brown, brown black, and black. The spores are found is dominated by the color of black that is 337 spores, then the color of red being the color of most little found which amounted to a total of 15 spores.